Tata Kelola Air Dalam Prespektif Islam - Yeni Hendriyani; Ahmad Hasan Ridwan (Syntax Corporation Indonesia, 2022)
Water is one of the most important natural resources in human life. You can imagine what life would be like if there was no water. The rate of population growth which is inversely proportional to the availability of water has caused a water crisis. The water crisis has made people aware of the need for efforts to raise awareness about the importance of water and its maintenance. Water as one of the fulfillment of needs, as well as a means of worship requirements. To what extent Islam views water as a very urgent resource, it can be seen from the explanation of the rules for managing these resources. The research method this time is a qualitative research that emphasizes research that uses library materials as the main source (data). From this presentation, it can be seen that both Islam and the rule of law in Indonesia place water as a very important resource.